Effects of the Particle Size and Gasification Atmosphere on the Changes in the Char Structure during the Gasification of Mallee Biomass - Wang, Shuai; Wu, L.; Hu, X.; Zhang, Lei; Li, Tingting; Li, Chun-Zhu (American Chemical Society, 2018)
The purpose of this study is to investigate the evolution of the char structure during the gasification of mallee biomass in different particle size ranges (up to 5.6 mm) in two atmospheres (15% H2O balanced with Ar and pure CO2) in a fluidized-bed reactor. Fourier transform Raman spectroscopy was used to characterize the char structure. The first-order Raman spectra in the range between 800 and 1800 cm-1and the second-order Raman spectra in the range between 2200 and 3300 cm-1were deconvoluted to understand the detailed structural features of char. Our results show that the differences in the intraparticle heat and mass transfer between small and big particle sizes during pyrolysis are largely responsible for the difference in the char yield during gasification, and the intraparticle gas diffusion is not a rate-limited step during the subsequent gasification of char for the conditions used in this study. As revealed by Raman spectroscopy, there are no significant changes in the overall Raman-active oxygen species and aromatic ring systems among different biomass particle sizes during gasification. The differences in the cross-linking density of char as indicated by the 2S band in the second-order Raman spectra between gasification in steam and CO2atmospheres again demonstrate that char-H2O and char-CO2follow different reaction pathways.